Actinic lichen planus in an 11-year-old boy. - Puri, N. (European Journal of Pediatric Dermatology, 2011)
An 11-year-old boy with dark phototype was first observed due to the presence of multiple, annular, dark patches of the face (Fig. 1), forearms and shins, which developed progressively in the previous year. The histological examination (Fig. 2) showed compact, wedge-shaped hypergranulosis, elongated epidermal crests, coarse basal cell vacuolization and Civatte bodies. A band-like inflammatory lymphohistiocytic infiltrate and melanic pigment were present in the papillary dermis. A direct immunofluorescence of exposed skin was negative. These data led to the final diagnosis of actinic lichen planus and to prescribe topical corticosteroids and sunscreens. The lesions partially improved in three months, but relapsed after sun exposure.